Development of EMG circuit to study the relationship between Flexor Digitorum Superficialis muscle activity and hand grip strength - Haja Mohideen, Ahmad Jazlan; Sidek, Shahrul Na'im (2011)
Hand grip strength plays a vital role in performing basic daily tasks such as holding an object. These tasks require a lot of effort from the muscles in the forearm. In this paper, we study the relationship between the muscular effort of the flexor muscles in the forearm and hand grip strength. In order to do that, an electronic circuit was constructed to amplify and filter the electromyogram (EMG) signals measured from the Flexor Digitorum Superficialis (FDS) muscle. The EMG signals measured from the FDS are used to study the relationship between muscular effort of the flexor muscles in the forearm and hand grip strength. EMG signals were measured from the subject while he applied minimum, intermediate and maximum hand grips on a hand gripper. The results show that EMG frequency from the FDS increase with increased hand grip strength. This information relating EMG from flexor muscles to hand grip strength is useful to be used in hand rehabilitation devices to estimate suitable resistance to be provided to patients during rehabilitation routines. Each stage of the circuit development is described in detail so that this experiment can be easily reproduced by others.